Refugees and Migrants in Contemporary Film, Art and Media - Bayrakdar, Deniz; Burgoyne, Robert (Book collections on Project MUSE., 2022)
Migration in the 21st century is one of the pre-eminent issues of our present historical moment, a phenomenon that has acquired new urgency with accelerating climate change, civil wars, and growing economic scarcities. Refugees and Migrants in Film, Art and Media consists of eleven essays that explore how artists have imaginatively engaged with this monumental human drama, examining a range of alternative modes of representation that provide striking new takes on the experiences of these precarious populations. Covering prominent art works by Ai Weiwei and Richard Mosse, and extending the spectrum of representation to refugee film workshops on the island of Lesvos as well as virtual reality installations of Alejandro G. Iñárritu and others, the chapters included here focus on the power of aesthetic engagement to illuminate the stories of refugees and migrants in ways that overturn journalistic clichés.